Editorial : Introduction to the special issue on assessing children’s social emotional learning to guide improvement programs - Christopher J. Anthony; Illaria Grazzani; Stephen N. Elliott; Valeria Cavioni (International Journal of Emotional Education, 2024)
Although the COVID-19 Pandemic began in 2020, it continues to exert a negative impact on the social, emotional, behavioral, and academic wellbeing of many children and youth across the globe (e.g., Bell et al., 2023; Panchal et al., 2023) and throughout Europe (European Education and Culture Executive Agency, 2022). To address these significant needs, researchers, educators, and policymakers have continued to stress the importance of developing instructional and intervention programs that target children’s social and emotional learning (SEL) and emotional behavior concerns (EBC). Many examples of such programs exist in countries throughout Europe (e.g., Cefai, et al., 2018). A particularly notable example is the Promoting Mental Health at Schools (PROMEHS) program (Cefai et al., 2022). Such developments are promising as children and youth continue to need enhanced supports and schools represent an excellent setting to provide it to them.